Awareness of Colorectal Cancer and Attitudes Towards Its Screening Guidelines in Lebanon. Issue 1 (28th May 2019) - Tfaily, Mohamad Ali; Naamani, Dana; Kassir, Alaa; Sleiman, Sara; Ouattara, Mamadou; Moacdieh, Munir Paul; Jaffa, Miran A.
Background: Screening for colorectal cancer (CRC) provides an effective strategy for early detection and prevention of the disease; however, global screening rates are still low. Purpose: This study aims at assessing the awareness of CRC risk factors, warning signs, and attitudes towards CRC guidelines and screening modalities, in order to identify the barriers to and correlates of CRC screening in the Lebanese population. Methods: A self-administered questionnaire was distributed to 371 participants in the largest health care medical center in Lebanon. A validated 12- and 9-item Cancer Awareness Measurement questionnaire was used to assess participants' awareness of CRC risk factors and warning signs. Results: 83% and 67% of participants were not aware of CRC risk factors and warning signs, respectively, 15% have previously undergone CRC screening, 56% were aware of the necessity for screening, and 43% were willing to undergo screening. Factors affecting awareness of the necessity for CRC screening, past screening and willingness to screen included awareness of risk factors and warning signs, undergoing regular physician check-ups, having a family physician as a primary source of knowledge of CRC, and knowing a family member or friend diagnosed with CRC. Barriers to screening were related to participants' evaluation of the screening technique and misconceptions about this disease. Conclusion: Serious active measures should be taken by health care sectors, authoritative groups, primary care physicians, and awareness campaigns to fill the gap in awareness of this disease and to alleviate the barriers and misconceptions around it.